Energy and nutrient intake in preschool and school age Mexican children: National Nutrition Survey 1999 - Barquera Simón; Rivera Juan A; Safdie Margarita; Flores Mario; Campos-Nonato Ismael; Campirano Fabricio (Instituto Nacional de Salud Pública, 2003)
OBJECTIVE: To estimate energy and nutrient intake and adequacy in preschool and school age Mexican children, using the National Nutrition Survey 1999 (NNS-1999). MATERIAL AND METHODS: Twenty four-h dietary recalls from pre-school (n=1 309) and school (n=2 611) children obtained from a representative sub-sample of the NNS-1999 were analyzed. Intakes and adequacies were estimated and compared across four regions, socio-economic strata, and between urban and rural areas, and indigenous vs. non-indigenous children. RESULTS: Median energy intake in pre-school children was 949 kcal and in school children 1 377 kcal, with adequacies <70% for both groups. Protein adequacy was >150% in both age groups. The North and Mexico City regions had the highest fat intake and the lowest fiber intake. Children in the South region, indigenous children, and those in the lowest socio-economic stratum had higher fiber and carbohydrate intakes and the lowest fat intake. These children also showed the highest risks of inadequacies for vitamin A, vitamin C, folate, iron, zinc and calcium. CONCLUSIONS: Mexico is experiencing a nutrition transition with internal inequalities across regions and socio-economic strata. Food policy must account for these differences in order to optimize resources directed at social programs.